2015
DOI: 10.5937/ekopolj1501073z
|View full text |Cite
|
Sign up to set email alerts
|

Cluster development in rural areas

Abstract: SummaryThe interest in creating a base-line for development patterns of clusters and clusters '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Clusters arise and endure because firms that may be competing also share similar market ambitions and seek to leverage the cluster members' shared goals and aspirations by inter‐firm cooperation (Felzensztein, Gimmon, and Carter ). Zheliazkov et al () noted that clusters are generally perceived as drivers of economic growth. However, to be sustainable there needs to be a balance between cooperation, cluster development, support initiatives, competitive rivalry, and differentiation.…”
Section: Theoretical Insights: Clusters and Internationalizationmentioning
confidence: 99%
“…Clusters arise and endure because firms that may be competing also share similar market ambitions and seek to leverage the cluster members' shared goals and aspirations by inter‐firm cooperation (Felzensztein, Gimmon, and Carter ). Zheliazkov et al () noted that clusters are generally perceived as drivers of economic growth. However, to be sustainable there needs to be a balance between cooperation, cluster development, support initiatives, competitive rivalry, and differentiation.…”
Section: Theoretical Insights: Clusters and Internationalizationmentioning
confidence: 99%
“… 2. Forms of inter-firm cooperation considered in the literature include informal inter-firm networks (Martin-Rios and Erhardt, 2016), (firm) networks (Gronum et al, 2012; Lechner and Dowling, 2003; Shaw, 2006), small business groups (Lechner and Leyronas, 2009), social networks (BarNir and Smith, 2002; Zhang, 2010), entrepreneurial networks (Drakopoulu Dodd et al, 2002; Hampton et al, 2009; Jack et al, 2010), local networks/clusters (Boehe, 2013; Lechner and Leyronas, 2012; Zheliazkov et al, 2015), strategic networking (Miller et al, 2007), business associations (Bennett et al, 2007), policy-driven networks (Lockett et al, 2013), innovation networks (Gardet and Fraiha, 2012; McAdam et al, 2014), external relationships (Lasagni, 2012; Street and Cameron, 2007), inter-firm cooperation (Hanna and Walsh, 2008), (inter-firm) alliances (Van Gils and Zwart, 2009) and so forth. A variety of cooperation forms increases the difficulties arising from the interchangeable use of terms such as alliances, networks and cooperative ventures (Hanna and Walsh, 2008).…”
mentioning
confidence: 99%
“…Holub-Iwan (2012) in his research found that cluster structures can be very diverse and it depends on the economic potential of the cluster members. Certain authors (Zheliazkov et al., 2015) emphasize that, since 2000, researchers examined the characteristics of clusters, the ways of identifying them and their influence on the market environment. Nordin (2003) concurrently observe clusters as a group of companies that are forming alliances and cooperating and as competitors in certain areas.…”
Section: ) Has Determined Clusters As Geographic Concentrations Of mentioning
confidence: 99%